Near infrared light mitigates cerebellar pathology in transgenic mouse models of dementia. (30th March 2015) - Purushothuman, Sivaraman; Johnstone, Daniel M.; Nandasena, Charith; Eersel, Janet van; Ittner, Lars M.; Mitrofanis, John; Stone, Jonathan
Highlights: Near infrared light (NIr) is neuroprotective to various models of brain disease. We test whether NIr mitigates cerebellar pathology in mouse models of dementia. NIr reduces β-amyloid deposition and neurofibrillary tangles in cerebellar cortex. NIr mitigates oxidative stress and mitochondrial dysfunction in cerebellum. Findings suggest NIr provides widespread protection of the brain in dementia models. Abstract: We previously reported that Alzheimer-related pathology in cerebral cortex of APP/PS1 and K3 tau transgenic mouse strains is mitigated by near infrared light (NIr). Here, we extend these observations to the cerebellum. One month of NIr treatment mitigated the deposition of β-amyloid in cerebellar cortex of APP/PS1 mice, and the formation of neurofibrillary tangles, the hyperphosphorylation of tau, the damage caused by oxidative stress and the downregulation of cytochrome oxidase expression by Purkinje cells in the cerebellar cortex of K3 mice. These findings show the ability of NIr to mitigate degeneration in many – probably all – regions of the mouse brain.